The Contribution of Photon, Z Boson, Higgs, Radion and Unparticle to the Processes in Randall-Sundrum Model - Thuy, Dao Thi Le; Mai Dung, Le (VNU Journal of Science: Mathematics - Physics; Vol 40 No 1DO - 10.25073/2588-1124/vnumap.4867, 2024)
T he fundamentally well-known process of Bhabha  is studied from the theoretical view of unparticle physics in the prominent Randall-Sundrum model. The cross-sections independently for photon ( γ ), Z boson ( Z ) , vector unparticle (U μ ), Higgs ( h ), radion ( ), and scalar unparticle ( U ) exchange are calculated and evaluated. Numerical calculations showed that the contribution of unparticle exchange dominates in very high energy regions. While the standard model exchanges as γ and Z are predominant in the lower energy region, h and contribution is very small in comparison with the other exchanges. The results are plotted in the energy ranges available in the present designs of accelerators and near future energy upgrades of the International Linear Collider (ILC) and The Compact Linear Collider (CLIC).